KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA GAMBAR BERSERI PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS III SEKOLAH DASAR - Mita, Mita; Khoiri, Ahmad; Rudiansyah, Eko (FKIP UM Pontianak, 2026)
This study aims to analyze the early reading ability of third-grade elementary school students through the use of serial picture media in Indonesian language learning. The focus of the study includes the ability to recognize picture sequences, read simple sentences, and compose stories based on a series of pictures. This research employed a qualitative approach with a descriptive method. The research subjects consisted of the third-grade homeroom teacher and third-grade students at SDN 28 Kelakik. Data were collected through interviews, observations, and documentation to obtain an in-depth understanding of the learning process and outcomes. The results indicate that serial picture media help students understand picture sequences more systematically, improve accuracy and fluency in reading simple sentences, and support students’ ability to compose simple stories based on pictures. Overall, serial picture media contribute positively to improving the early reading ability of third-grade students.